Effects of dynamic controlled atmosphere and initial low oxygen stress on superficial scald of 'Granny Smith' apples and 'Packham's Triumph' pears - Ramokonyane, Tlou Melrose (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.